2019
DOI: 10.5578/turkjsurg.4126
|View full text |Cite
|
Sign up to set email alerts
|

Routine histopathological examination of gallbladder specimens after cholecystectomy: Is it time to change the current practice?

Abstract: Objective: Routine histopathological examination of all gallbladder specimens, regardless of the clinical characteristics of the patient or macroscopic aspect of the gallbladder, is the current approach to detect the presence of gallbladder carcinoma. The aim of the present study was to assess whether or not it would be safe to adopt a policy of processing only gallbladder specimens with preoperative or intraoperative suspicion for malignancy without compromising patient safety. Material and Methods: From Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The incidence of most benign pathologies [ Table 2 ] were similar to the previous reports. [ 17 18 ] However, the incidence of xanthogranulomatous cholecystitis (3.45%) was found to be higher in the present series than most other reported series. Limaiem F et al ,[ 18 ] reported 0.30% and Benkhadoura M et al .…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The incidence of most benign pathologies [ Table 2 ] were similar to the previous reports. [ 17 18 ] However, the incidence of xanthogranulomatous cholecystitis (3.45%) was found to be higher in the present series than most other reported series. Limaiem F et al ,[ 18 ] reported 0.30% and Benkhadoura M et al .…”
Section: Discussioncontrasting
confidence: 72%
“…[ 18 ] Benkhadoura M et al . [ 17 ] reported a higher incidence of chronic cholecystitis as 81.60% in their series.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies conducted in other surgical fields have reported similar analyses on hernia sacs, intervertebral discs, adenoid tissue, and gallbladders with mixed results on the cost effectiveness 13) . For example, The College of American Pathologists 14) continues to recommend microscopic examination of abdominal hernias, but has now left submission of inguinal hernias up to the discretion of the pathologist 15) . Similarly, submission of gallbladder specimens to detect the presence of gallbladder carcinoma is still standard procedure; however, because many patients with cancer are captured either preoperatively or intraoperatively, the process is falling out of favor 16) .…”
Section: Introductionmentioning
confidence: 99%